Work conditions as predictors of Swedish occupational therapists' occupational balance. - Håkansson, Carita; Lexén, Annika (Scandinavian Journal of Occupational Therapy, 2023)
There is little knowledge of how organizational and social work environmental conditions impact workers' perceptions of occupational balance. The aim of the present study was to investigate organizational and social work environmental conditions as predictors of Swedish occupational therapists' perceptions of occupational balance. This prospective study collected data twice, with a one-year interval, and used a web survey. The present study included 1835 participants. Logistic regression analysis was used to analyze the work predictors of occupational balance. A reasonable workload, high control, and high reward predicted high occupational balance. Having no children living at home, a satisfactory financial situation, and being physically active also predicted high occupational balance. A reasonable workload, high control and high reward predicted occupational balance among the occupational therapists. All these factors may be of importance for a sustainable working life for occupational therapists. This knowledge can support occupational therapists in the development of interventions at the work place, with focus on the workload and the resources (control and reward), to promote employees' occupational balance.